A Mobile App to Prevent Depression Among Low-Income Primary Care Patients in the Dominican Republic: Sociocultural Adaptations. (July 2020) - Caplan, Susan; Sosa Lovera, Angelina; Veloz Comas, Esther; Attilus, Jonas
Introduction: Mental health mobile apps (MHapps) can provide depression treatment to people worldwide who do not have access to care, but few apps are culturally targeted to the population. In this series of studies, we described sociocultural considerations of MHapp development, and we explored participants' perceptions of acceptability, usability, and cultural relevance of the MHapp.Method: Individual interviews were conducted in three separate primary care sites in the Dominican Republic among convenience samples of staff and patients ( n = 23, 18, and 21, respectively), using mixed methods of data collection.Results: Modifications were made during the iterative design process to reflect user preferences, which included a female gendered voice, the addition of animations, and changes to the psychoeducational content.Discussion: Primary care patients reported strong interest in MHapps due to its convenience, privacy, and affordability. Our findings support the necessity of detailed examination of user preferences to develop culturally congruent MHapp psychoeducation.